Pengaruh Permainan Margala Terhadap Peningkatan Motorik Kasar Anak Usia 5-6 Tahun di Paud Glory HKI Siualoumpu (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Based on the results of initial observations conducted by researchers at PAUD Glory HKI Siualuompu regarding margala games, the PAUD does not use margala games but still uses lego media, swing games, slides, catwalks, puzzles. The author sees that there are still shortcomings in the development of margala games in that children's gross motor development has not developed optimally. The aim of this research is to determine the effect of margala games on improving gross motor skills in children aged 5-6 years at PAUD Glory HKI Siualoumpu. The method used in this research is a descriptive quantitative research method. The population was all children aged 5-6 years at PAUD Glory HKI Siualuompu, totaling 45 people and a sample of 23 people was determined using a non-probability sampling technique, namely purposive sampling. Data was collected using a positive closed questionnaire of 20 items. The results of data analysis show that there is a positive and significant influence of the margala game on improving the gross motor skills of children aged 5-6 years at PAUD Glory HKI Siualoumpu: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.598 > rtable( = 0.05, n = 23) = 0.413, thus it is known that there is a positive relationship between variable 2=21)= 2.080, thus there is a significant relationship between variable 9.66"+0.71X. Thus Ha is accepted and H0 is rejected.